Should Faustmann forecast climate change? - Johan Gars; Daniel Spiro (Center for Economic Studies and ifo Institute (CESifo), 2019)
Climate change is predicted to substantially alter forest growth. Optimally, forest owners should take these future changes into account when making rotation decisions today. However, the fundamental uncertainty surrounding climate change makes predicting these shifts hard. Hence, this paper asks whether forecasting them is necessary for optimal rotation decisions. While climate-change uncertainty makes it theoretically impossible to calculate expected profit losses of not forecasting, we suggest a method utilizing Monte-Carlo simulations to obtain a credible upper bound on these losses. We show that an owner following a rule of thumb - ignoring future changes and only observing changes as they come - will closely approximate optimal management. If changes are observed without too much delay, profit losses and errors in harvesting are negligible. This means that the very complex analytical problem of optimal rotation with changing growth dynamics can be simplified to a sequence of stationary problems. It also implies the argument that boundedly-rational agents may behave “as if” being fully rational has traction in forestry.
Keywords: C60; D81; Q23; Q54; 330; climate change; decision making under uncertainty; forestry; quantitative methods